Seasonal variations in pm2g air pollutants and impact on preterm birth rate in Kampala: A Retrospective Cohort (2020)
There is a growing body of evidence linking air pollution to negative births outcomes, but few studies have explored the relationship of air pollution on negative births outcomes such as preterm birth in Africa. Identifying the association between PM2 5 and preterm births will be a good starting point for intervention and policy changes on air pollution reduction methods. The study aimed to determine the association between seasonal variation in PM25 and preterm births in Kampala Uganda. Retrospective cohort study was carried out by collecting birth outcomes data from District Health Information System 2 (DHIS2) database, with the authority of Kampala Capital City Authority (KCCA). PM2.5 data were collected from US Embassy monitoring station from January 2018 to December 2019. Association between seasonal variation in PM2.5 and preterm births were found using STATA 13.0 version. This study showed a seasonal trend in PM2.5 level which was very high between the range of 56-72 ugym1 in the two dry seasons of the year 2018 and 2019. It was found lower in both wet seasons of the year 2018 and 2019 within the range of 40-52 pg/m3. The regression analysis showed that there is a strong association between each 10 unit increase in PM2.5 and preterm births in second dry season of 2018 and the first dry season of 2019 (p<0.000). The results of this study support with evidence the relationship between PM2.5 air pollutant and preterm births, especially in dry seasons